2017
DOI: 10.1142/s0192415x17500781
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhizaLipophilic Fraction Attenuates Oxidative Stress in Diabetic Nephropathy through Activation of Nuclear Factor Erythroid 2-Related Factor 2

Abstract: Diabetic nephropathy (DN) is a common cause of chronic kidney disease and end-stage renal disease, which can be triggered by oxidative stress. In this study, we investigated the renoprotective effect of the ethyl acetate extract of Salvia miltiorrhiza (EASM) on DN and examined the underlying molecular mechanism. We observed that EASM treatment attenuated metabolic abnormalities associated with hyperglycemic conditions in the experimental DN model. In streptozotocin (STZ)-induced mice, EASM treatment reduced al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Evidence was recently reported that the ethyl acetate extract of Salvia miltiorrhiza (commonly known as Danshen) attenuates oxidative stress in the streptozotocin-treated mouse model of diabetic nephropathy via upregulated expression of Nrf2 (An et al, 2017 ). Triptolide, the main active ingredient of Tripterygium wilfordii Hook.…”
Section: Traditional Chinese Medicines For Treating Ckdmentioning
confidence: 99%
“…Evidence was recently reported that the ethyl acetate extract of Salvia miltiorrhiza (commonly known as Danshen) attenuates oxidative stress in the streptozotocin-treated mouse model of diabetic nephropathy via upregulated expression of Nrf2 (An et al, 2017 ). Triptolide, the main active ingredient of Tripterygium wilfordii Hook.…”
Section: Traditional Chinese Medicines For Treating Ckdmentioning
confidence: 99%
“…Besides these pharmacological effects, a growing body of data indicated that SMRR potently activated intracellular antioxidant enzymes, upregulated endogenous antioxidants, and scavenged intracellular ROS. Therefore, SMRR demonstrated potential therapeutic effects against oxidative stress-induced diseases, such as cardiovascular diseases, inflammation, and renal disease [ 33 35 ].…”
Section: Salviae Miltiorrhizae Radix Et Rhizoma (Smrr)mentioning
confidence: 99%
“…Oxidative stress has been implicated in the onset and promotion of nephropathy, and the modulation of Nrf2 is an efficient strategy for the therapy of renal diseases [ 84 ]. Ethyl acetate extract of SMRR enhanced the expression of Nrf2 and inhibited ROS production in high-glucose-induced mouse mesangial cells (MMCs) [ 33 ]. It reduced albuminuria and alleviated renal damage in streptozocin-induced mice.…”
Section: Nrf2-based Therapeutic Potential Of Smrr and Its Constitumentioning
confidence: 99%
“… 160 For instance, Tanshinone IIA, a di-terpenoid isolated from SM, showed antioxidant benefit by activating the Nrf2 signaling pathway, improving the metabolic profile and exhibiting potent renoprotective effects, 160 and the lipophilic fraction attenuated oxidative stress in diabetic nephropathy. 161 …”
Section: Resultsmentioning
confidence: 99%